2016
DOI: 10.3354/meps11730
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting ocean warming impacts on seabird demography: a case study on the European storm petrel

Abstract: Bottom-up climatic forcing has been shown to be influential for a variety of marine taxa, but evidence on seabird populations is scarce. Seasonal variation in environmental conditions can have an indirect effect on subsequent reproduction, which, given the longevity and single-brooding of seabirds, may affect population dynamics. Our study focuses on linking the effect of oceanographic conditions (from 1991 to 2013) to the fecundity and consequently population growth rate of the Mediterranean subspecies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 98 publications
(124 reference statements)
1
8
0
Order By: Relevance
“…We did not investigate the influence of environmental conditions on the probability to skip breeding in this study due to the already high complexity of our model that accounted for individual heterogeneity on top of imperfect detection and state assignment probabilities. However, we suspect intermittent breeding to be closely associated with unfavourable environmental conditions as reported in other long-lived species (Cubaynes et al, 2011;Forcada et al, 2008;Soldatini et al, 2016). In particular, Van den Hoff et al (2014) showed that, in this population of elephant seals, the number of breeding seals varied substantially between years and that this variation was related to environmental conditions.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We did not investigate the influence of environmental conditions on the probability to skip breeding in this study due to the already high complexity of our model that accounted for individual heterogeneity on top of imperfect detection and state assignment probabilities. However, we suspect intermittent breeding to be closely associated with unfavourable environmental conditions as reported in other long-lived species (Cubaynes et al, 2011;Forcada et al, 2008;Soldatini et al, 2016). In particular, Van den Hoff et al (2014) showed that, in this population of elephant seals, the number of breeding seals varied substantially between years and that this variation was related to environmental conditions.…”
Section: Discussionsupporting
confidence: 64%
“…Reproductive skipping has also been reported to be an adaptive tactic to offset reproductive costs under severe environmental conditions (Cubaynes, Doherty, Schreiber, & Gimenez, 2011;Forcada, Trathan, & Murphy, 2008;Soldatini, Albores-Barajas, Massa, & Gimenez, 2016) or to be the unavoidable outcome of other events (e.g. breeding dispersal Reed, Harris, & Wanless, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Marine megafauna such as seabirds, sea turtles and marine mammals are ideal candidates for understanding and communicating the impacts of climate change on marine ecosystems (Durant et al., ; Hawkes, Broderick, Godfrey, & Godley, ; Lascelles et al., ; Moore, ; Moore & Huntington, ; Sydeman, Poloczanska, Reed, & Thompson, ; Sydeman, Thompson, & Kitaysky, ). Many populations appear to have consistent migration pathways (Horton et al., ), and may be having difficulty in adapting to shifts in environmental conditions (Ainley et al., ; Barbraud et al., ; Hazen et al., ; Jenouvrier et al., ; MacLeod, ; Soldatini, Albores‐Barajas, Massa, & Gimenez, ; Sprogis, Christiansen, Wandres, & Bejder, ; Sydeman et al., ) and to bottom‐up effects caused by changes in the distribution and abundance of prey species (Evans & Bjørge, ; Neeman, Robinson, Paladino, Spotila, & O'Connor, ; Sydeman et al., ). Resulting population declines worldwide may have dangerous top‐down effects on the structure, function and stability of marine food webs (Estes et al., ; McCauley et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We included a non-breeder state in our models [ 30 ] to account more accurately for the proportion of the population that skip a breeding year, which may be an artifact of individual lower body condition or unfavorable environmental conditions, such as a post-El Niño year [ 35 , 36 ]. From the E-Surge modelling exercise, we estimated that 12% of the population in the colony were non-breeders, a percentage we expect would be lower in years with favorable environmental conditions that increase the likelihood of reproduction.…”
Section: Discussionmentioning
confidence: 99%